Preoperative assessment of microvascular invasion risk using gadoxetate-enhanced MRI for predicting outcomes after liver transplantation for single hepatocellular carcinoma within the Milan criteria - Cha, Dong Ik; Kang, Tae Wook; Jeong, Woo Kyoung; Kim, Jong Man; Choi, Gyu Seong; Joh, Jae Won; Yi, Nam Joon; Ahn, Soo Hyun (European Radiology, 2024)
Objective: To compare therapeutic outcomes after liver transplantation (LT) between hepatocellular carcinomas (HCC) with low and high risk for microvascular invasion (MVI) within the Milan criteria evaluated preoperatively. Methods: Eighty patients with a single HCC who underwent LT as the initial therapy between 2008 and 2017 were included from two tertiary referral medical centers in a HBV-predominant population. A preoperative MVI-risk model was used to identify low- and high-risk patients. Recurrence-free survival (RFS) after LT between the two risk groups was compared using Kaplan-Meier curves with the log-rank test. Prognostic factors for RFS were identified using a multivariable Cox hazard regression analysis. Results: Eighty patients were included (mean age, 51.8 years +/− 7.5 [standard deviation], 65 men). Patients were divided into low-risk (n = 64) and high-risk (n = 16) groups for MVI. The RFS rates after LT were significantly lower in the MVI high-risk group compared to the low-risk group at 1 year (75.0% [95% CI: 56.5–99.5%] vs. 96.9% [92.7–100%], p = 0.048), 3 years (62.5% [42.8–91.4%] vs. 95.3% [90.3–100%], p = 0.008), and 5 years (62.5% [42.8–91.4%] vs. and 95.3% [90.3–100%], p = 0.008). In addition, multivariable analysis showed that MVI high risk was the only significant factor for poor RFS (p = 0.016). Conclusion: HCC patients with a high risk of MVI showed significantly lower RFS after LT than those without. This model could aid in selecting optimal candidates in addition to the Milan criteria when considering upfront LT for patients with HCC if alternative treatment options are available. Clinical relevance statement: High risk for microvascular invasion (MVI) in hepatocellular carcinoma patients lowered recurrence-free survival after liver transplantation, despite meeting the Milan criteria. Identifying MVI risk could aid candidate selection for upfront liver transplantation, particularly if alternative treatments are available. Key Points: • A predictive model-derived microvascular invasion (MVI) high- and low-risk groups had a significant difference in the incidence of MVI on pathology. • Recurrence-free survival after liver transplantation (LT) for single hepatocellular carcinoma (HCC) within the Milan criteria was significantly different between the MVI high- and low-risk groups. • The peak incidence of tumor recurrence was 20 months after liver transplantation, probably indicating that HCC with high risk for MVI had a high risk of early (≤ 2 years) tumor recurrence.
Keywords: Carcinoma, Hepatocellular; Gadolinium DTPA; Humans; Liver Neoplasms; Liver Transplantation; Magnetic Resonance Imaging; Male; Middle Aged; Neoplasm Invasiveness; Neoplasm Recurrence, Local; Prognosis; Retrospective Studies; Biomarkers, tumor; Carcinoma, hepatocellular; Liver neoplasms; Prognosis